EKSISTENSI DAN KEDUDUKAN PERATURAN PRESIDEN DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Prischa Listiningrum (Arena Hukum, 2019)
AbstractThis article aims to explore the history of the existence of the Presidential Decree ("Perpres") in the hierarchy of laws and regulations in Indonesia. Inspired by the controversy over the position of the Perpres which had become a heated debate in the Special Committee Meeting (Draft Bill) concerning the Establishment of Invitation Laws. In fact, the House of Representatives (DPR) had proposed the abolition of Perpres from the hierarchy of laws and regulations. This is a normative legal research that uses statute approach, historical approach, and conceptual approach. This research attempts to find the history of the existence of Perpres in Indonesia. Which was then followed by an analysis of the position of the Perpres in the hierarchy of laws and regulations, both as a regulation of delegation (delegated legislation), and as "Independent Perpres", along with the problems of the test. AbstrakArtikel ini bertujuan untuk menelisik sejarah keberadaan Peraturan Presiden (â€œPerpresâ€) dalam hierarki peraturan perundang-undangan di Indonesia. Terinspirasi dari kontroversi kedudukan Perpres yang sempat menjadi perdebatan yang cukup hangat dalam Rapat Panitia Khusus (Pansus) Rancangan Undang-Undang (RUU) tentang Pembentukan Peraturan Perundang Undangan. Dengan menggunakan penelitian hukum normatif yang menggunakan pendekatan peraturan perundang-undangan, pendekatan sejarah, dan pendekatan konsep, penelitian ini berusaha untuk menemukan sejarah eksistensi Perpres di Indonesia. Kemudian dilanjutkan dengan analisis tentang kedudukan Perpres dalam hierarki peraturan perundang-undangan, baik sebagai peraturan delegasi (delegated legislation), maupun sebagai â€œPerpres Mandiriâ€, beserta problematika pengujiannya.